Safe - Tomney, Ed (<<The>> Criterion Collection, 2014)
"Julianne Moore gives a breakthrough performance as Carol White, a Los Angeles housewife in the late 1980s who comes down with a debilitating illness. After the doctors she sees can give her no clear diagnosis, she comes to believe that she has frighteningly extreme environmental allergies. A profoundly unsettling work from the great American director Todd Haynes, Safe functions on multiple levels: as a prescient commentary on self-help culture, as a metaphor for the AIDS crisis, as a drama about class and social estrangement, and as a horror film about what you cannot see. This revelatory drama was named the best film of the 1990s in a Village Voice poll of more than fifty critics." [criterion.com]
Aspect ratio 1.85:1 - New 4K digital restoration
Orig.: Großbritannien, USA 1995
Enth. audio commentary featuring Haynes, actor Julianne Moore, and producer Christine Vachon ; new conversation between Haynes and Moore "The suicide", a 1978 short film by Haynes [22 Min.] ; new interview with Vachon ; trailer ; an essay by critic Dennis Lim